Study of Morbidity Pattern and Its Associated Factors among Migrant Workers Residing in the Field Practise Area of a Tertiary Care Hospital in Mangalore: A Cross-Sectional Study (Indian Journal of Public Health Research & Development, 2020)
Introduction: Migration is a process of social change due to which a person moves from one culturalsetting to another to settle for a longer period or permanently. The collapse of rural livelihood forces theworkers to migrate. As migrants do several types of jobs, there are high chances of morbidities. Methods:A cross-sectional study was done on 392 people selected using simple random sampling in Lingapayyakaduusing pre-tested and semi-structured questionnaire. SPSS software was used for data analysis. Results:68.7% were males and rest females. 80.9% had some form of acute morbidity in previous 3 months whereas16% were suffering from chronic morbidities. Age (p = 0.046), working hours per day (p = 0.017) andoccupation (p = 0.047) had significant association with acute morbidity while age, (p < 0.01) sex (p =0.046) and education level (p < 0.01) had significant association with chronic morbidity. Conclusion: Majoracute morbidity was musculo-skeletal disorders and age, working hours and occupation had significantassociation while hypertension was the major chronic morbidity with age, sex and education level havingsignificant association with chronic morbidity
Keywords: Migration, Musculo-skeletal disorders, Acute morbidity, Chronic morbidity, Risk factors